(untitled) (Theatrum historiae, 2012)
The newly collected information sheds light upon the social origins and ties of Johann Heinrich Dienebier (1677–1748) and makes us familiar with his 27 years of service for Johann Wenzel Gallas (1671–1719), an important and wealthy aristocrat in the Habsburg monarchy. This information enables us to acknowledge the erudition and designing genius of this creative (and so far marginalised) building copyist (Bauschreiber) of the Prague Castle.